2012
DOI: 10.3892/ijmm.2012.966
|View full text |Cite
|
Sign up to set email alerts
|

EGCG suppresses prostate cancer cell growth modulating acetylation of androgen receptor by anti-histone acetyltransferase activity

Abstract: Abstract. Manipulating acetylation status of key gene targets is likely to be crucial for effective cancer therapy. In this study, we utilized green tea catechins, epicatechin (EC), epigallocatechin (EGC) and epigallocatechin-3-gallate (EGCG) to examine the regulation of androgen receptor acetylation in androgen-dependent prostate cancer cells by histone acetyltransferase (HAT) activity. EC, EGC and EGCG induced prostate cancer cell death, suppressed agonist-dependent androgen receptor (AR) activation and AR-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 18 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…The HDAC or HAT inhibitory activity of EGCG has been shown to lead to hyper- or hypo-acetylation of non-histone proteins such as p53, p65, androgen and estrogen receptors [52, 5456]. Even though in our study p65 acetylation was not diminished by EGCG (data not shown) as demonstrated previously [52], we found that EGCG can reduce the binding of p65 and p300 to the promoter region of NF-κB-regulated genes with an increased recruitment of HDAC1/2.…”
Section: Discussionmentioning
confidence: 99%
“…The HDAC or HAT inhibitory activity of EGCG has been shown to lead to hyper- or hypo-acetylation of non-histone proteins such as p53, p65, androgen and estrogen receptors [52, 5456]. Even though in our study p65 acetylation was not diminished by EGCG (data not shown) as demonstrated previously [52], we found that EGCG can reduce the binding of p65 and p300 to the promoter region of NF-κB-regulated genes with an increased recruitment of HDAC1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, agents or natural products that target those enzymes may also interfere with nuclear translocation of AR and indirectly inhibit AR mediated gene expression. For instance, the green tea derived EGCG, has been demonstrated to inhibit acetyltransferase activity up to 80% when used at a concentration of 25 µM [100]. Treatment with EGCG resulted in reduced AR acetylation and impeded androgen-mediated nuclear translocation of AR in PCa cell lines [100].…”
Section: Natural Products Against Pcamentioning
confidence: 99%
“…For instance, the green tea derived EGCG, has been demonstrated to inhibit acetyltransferase activity up to 80% when used at a concentration of 25 µM [100]. Treatment with EGCG resulted in reduced AR acetylation and impeded androgen-mediated nuclear translocation of AR in PCa cell lines [100]. These effects were confirmed in vivo using a PCa xenograft model [34].…”
Section: Natural Products Against Pcamentioning
confidence: 99%
“…EGCG acted at multiple levels including inhibiting interdomain N-C termini interaction, repressing the prostate cancer related mutant T877A and eventually inhibiting cancer cell growth. Lee et al [60] obtained similar results using a prostate cancer cell line in response to GT catechins. The researchers proposed that catechins modulated AR acetylation was modulated in the presence of GT catechins thereby inhibiting the translocation of the AR protein to the nucleus.…”
Section: Cancermentioning
confidence: 62%